Results of hyperbaric oxygenation in chronic wound healing – preliminary findings - Dzięgielewski, Piotr; Mikołajewska, Emilia; Goch, Aleksander (Medical Studies/Studia Medyczne, 2016)
Introduction: Improved wound healing decreases the risk of complications, increases the possibilities of further treatment, rehabilitation, and care, and improves the quality of life for the patients. Aim of the research: The aim of this paper is to present the outcomes of a study of chronic wound healing using hyperbaric oxygenation therapy (HBOT). The indirect aim of the study was also to assess correlations, i.e. statistical relationships, between observed changes of pain assessment, wound length, wound width, and transcutaneous oximetry and establish prognostic signs. Material and methods : Inclusion criteria meet the medical records of thirty adult patients with chronic wounds treated with HBOT. Wound length, wound width, and transcutaneous oximetry were measured before and after treatment. The pain was evaluated using the numerical rating scale before and after treatment. Results: The response to HBOT varied from good to excellent. Favourable and statistically significant changes were observed in all measured areas: pain assessment, wound length, wound width, and transcutaneous oximetry. Conclusions : The HBOT in adult patients with chronic wounds is an effective method of treatment. Age above 60 years, sex (male), and lack of obesity, if confirmed by further studies, can be useful prognostic signs. However, there is still little evidence. There is a strong need for more research.